Civic Development Among College Students at Southern Baptist Colleges and Universities. Issue 3 (27th May 2019) - Armstrong Conn, Cameron; Kim, Young K.
Abstract: Utilizing data from the 2009 College Senior Survey, this study measured and compared social agency and civic awareness among undergraduate students enrolled at four types of institutions: Baptist, CCCU, Catholic, and nonsectarian. Comparisons were made through paired-sample t -tests and ANOVA analyses. A series of separate multiple regressions were conducted to compare the patterns and predictors of civic development across institutional types. The results indicated that, despite the many features religious colleges share in common, student outcomes varied significantly between institutional types. Furthermore, student characteristics and college experiences contributed to students' civic development to varying degrees depending on the type of religious institution students attended.